2016
DOI: 10.1093/icesjms/fsw071
|View full text |Cite
|
Sign up to set email alerts
|

Food for thought: pretty good multispecies yield

Abstract: MSY principles for marine fisheries management reflect a focus on obtaining continued high catches to provide food and livelihoods for humanity, while not compromising ecosystems. However, maintaining healthy stocks to provide the maximum sustainable yield on a single-species basis does not ensure that broader ecosystem, economic, and social objectives are addressed. We investigate how the principles of a “pretty good yield” range of fishing mortalities assumed to provide >95% of the average yield for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 41 publications
0
60
0
Order By: Relevance
“…In practice OY has played out as being applied on a stock-by-stock basis, but it does not have to be done that way. Several jurisdictions are exploring or have proposed a systems approach to broaden the stock-specific application of OY (e.g., Mueter and Megrey 2006;Fogarty et al 2012;Fogarty 2014;Rosenberg et al 2014;Gaichas et al 2017;Rindorf et al 2017aRindorf et al , 2017b. When I advise governments and engage with counterparts in countries all around the world, for example, Norway, Canada, Australia, South Africa, New Zealand, Japan, the EU, Iceland, etc.…”
Section: Addressing Pragmatic Considerations Of System-level Thinkingmentioning
confidence: 99%
See 4 more Smart Citations
“…In practice OY has played out as being applied on a stock-by-stock basis, but it does not have to be done that way. Several jurisdictions are exploring or have proposed a systems approach to broaden the stock-specific application of OY (e.g., Mueter and Megrey 2006;Fogarty et al 2012;Fogarty 2014;Rosenberg et al 2014;Gaichas et al 2017;Rindorf et al 2017aRindorf et al , 2017b. When I advise governments and engage with counterparts in countries all around the world, for example, Norway, Canada, Australia, South Africa, New Zealand, Japan, the EU, Iceland, etc.…”
Section: Addressing Pragmatic Considerations Of System-level Thinkingmentioning
confidence: 99%
“…(cf. Mardle et al 2002;Marchal et al 2009;Dichmont et al 2010;Mesnil 2012;Patrick and Link 2015b;Rindorf et al 2017a), and broach the topic, not one has objected nor indicated that considering OY in aggregate is not allowed; rather, they typically tend to simply not think of it. This is also true in numerous intergovernmental organizations, such as the International Council for the Exploration of the Sea, Food and Agricultural Organization of the United Nations, or other regional fisheries management organisations -not one objects to aggregate OY on a legal basis.…”
Section: Addressing Pragmatic Considerations Of System-level Thinkingmentioning
confidence: 99%
See 3 more Smart Citations